Karakteristik Dewan Direksi, Komite Audit, dan Biaya Audit - Hendi, Hendi; Shella, Shella (E-Jurnal Akuntansi, 2022)
This study aims to examine the influence of the board of directors and the audit committee characteristic on audit fees. The independent variables were the size of the board of directors, the independence of the board of directors, women on the board of directors, the size of the audit committee, the independence of the audit committee, the financial expertise of the audit committee, the diligence of the audit committee, and women on the audit committee. The research population includes financial sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sample consists of 208 observations which were determined through purposive sampling. Data were analyzed by panel data regression. The analysis results showed that the size of the board of directors and the diligence of the audit committee had a significant positive influence on audit fees. Other variables have no significant effect on audit fees. Keywords: Audit Committee; Audit Fee; Board of Director; Financial Sector